Reconstructing Islamic Communication Ethics in the Algorithmic Public Sphere: From Information Abundance to Ethical Deficiency - Bambang Gunanti Hutabarat; Rubino Rubino; Muhammad Randicha Hamandia (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2026)
The rapid expansion of algorithm-driven digital platforms has transformed the contemporary public sphere into an environment characterized by information abundance while simultaneously experiencing a decline in ethical communication. Algorithmic recommendation systems prioritize engagement, personalization, and virality rather than truthfulness, responsibility, and public benefit, thereby encouraging misinformation, polarization, and ethical degradation. This article aims to reconstruct Islamic communication ethics as a normative framework capable of responding to ethical challenges within the algorithmic public sphere. The study employs a Systematic Literature Review (SLR) combined with a library research approach by synthesizing recent interdisciplinary literature concerning communication ethics, digital media, algorithmic governance, Islamic communication, and post-truth society. The findings demonstrate that the ethical crisis in algorithmic communication cannot be addressed solely through technological regulation because the problem fundamentally concerns the erosion of moral responsibility among communicators, platforms, and audiences. Islamic communication ethics provides an alternative ethical paradigm grounded in sidq (truthfulness), amanah (responsibility), tabayyun (verification), 'adl (justice), hikmah (wisdom), and maslahah (public benefit). These principles function not merely as individual moral virtues but as communicative norms capable of guiding digital interaction within algorithmically mediated environments. This study proposes a conceptual reconstruction that integrates Islamic ethical principles with contemporary communication philosophy to strengthen ethical resilience in the digital public sphere. The contribution of this article lies in offering an interdisciplinary ethical framework that connects Islamic communication ethics with algorithmic governance, thereby enriching contemporary discussions on digital communication ethics.